MENGKRITISI PENDIDIKAN ISLAM DI INDONESIA - Fuad Hilmi; Busro Busro (Edukasi Islami: Jurnal Pendidikan Islam, 2014)
Education is a necessity for all human beings, including Muslims in Indonesia. As the world's largest Muslim community, Muslims in Indonesia has made education an integral part in most of their lives. Islamic education as part of the daily needs of Muslims have been held in conjunction with the development of Muslims. Various models of Islamic education have been formulated and implemented, but there are still deficiencies that lead to the main goal of Islamic education is not achieved its full potential. Critics of Islamic education in Indonesia becomes urgent to improve the quality in the future.The approach used in this research is the study of educational policy based on the reality that occurs in the community, especially with regard to Islamic education in Indonesia.The study produced some facts about Islamic education in Indonesia, namely the low quality of educators (HR), management implemented a curriculum that is still sober and not integrated with the needs of the community. In addition, societal changes stimulated by globalization universe.Critics of Islamic education includes matters relating to internal and external factors. Internal factors are the low quality of human resources management and management of the pickup. The external factors are Globalization, Democratization, and Liberalization of Islam. Solutions that can be done to overcome this is to improve the quality of human resources practitioners of Islamic education, including curriculum management system update is based tauhidullah and strengthening Islamic values in the educational process.